A unified EMMS-based constitutive law for heterogeneous gas-solid flow in CFB risers. (2nd November 2020) - He, Mingming; Zhao, Bidan; Wang, Junwu
Highlights: Unified EMMS-based constitutive relation was proposed. A EMMS-based particle stress model was proposed. The effect of mesoscale structure was considered in the constitutive relation. The predicted granular temperature, pressure and viscosity are agreed with experimental data. Abstract: Energy minimization multi-scale (EMMS) drag model has been demonstrated to be very successful in quantifying the effect of mesoscale structure on the effective interphase drag force of heterogeneous gas-solid flow in circulating fluidized bed (CFB) risers, however, a corresponding model for the effective particle phase stress is not yet available. To this end, an EMMS drag model was extended to predict the granular temperature of particles inside the dilute phase and the dense phase as well as the granular temperature of clusters. A model for the effective particle phase stress was then developed based on the concept of multiscale analysis in EMMS model. It was shown that the experimentally measured granular temperature, granular pressure and granular viscosity as a function of mean solid concentration can be predicted reasonably well. The agreement demonstrates its effectiveness in the quantification of the effect of mesoscale structure on the particle phase stress, thus establishing a unified EMMS-based model for the constitutive law of heterogeneous gas-solid flow in CFB risers.